PENINGKATAN KINERJA USAHA KECIL JAMU MADURA : PEMANFAATAN TEKNOLOGI INFORMASI - Helmi Buyung Aulia Safrizal; Nirma Kurriwati (Universitas Trunojoyo Madura, 2016)
Madura’s economic conditions after the operation Suramadu bridge shows the development in a positive direction. SMEs in Madura Island as one of the business entity should contribute to further boost economic growth. One of the potential is a traditional Madura herbal medicine industry in Bangkalan that produce traditional herbal medicine with different types of products. Marketing efforts undertaken by herbal medicine SMEs is still very traditional and many deficiencies. Such as the distribution channels that are not well ordered, the price disparity, promotional programs that are not designed properly, marketing range is still limited in local area Madura and a little Java and the production and marketing process not in synchronization. The main weshes of the herbal medicine SMEs is an increase in the marketing area of herbal medicine product and the brand better known by the public. From the analysis of the marketing conditions and the requirement of SMEs then drafted a marketing model of herbal medicine SMEs by utilizing information technology such as e-commerce web to improve marketing performance solutions that will bring herbal medicine SMEs in Bangkalan Madura improving business continuity.